Sugammadex shortens the time to extubate and discharge from PACU in patients with tracheobronchial stenosis undergoing rigid bronchoscopy procedures: A retrospective cohort study - Lu, Xiaofei; Li, Tingting; Chen, Xu; Xu, Meiying; Wu, Jingxiang; Qiu, Yuwei (Frontiers in Anesthesiology, 2023)
Introduction Incomplete reversal of neuromuscular blocking drugs can delay patients' rapid recovery and lead to adverse events in the postoperative period, especially in high-risk patients. Sugammadex as a reversal agent, may offer distinct advantages to the scenario where residual neuromuscular blockade may be poorly tolerated. We aimed to investigate the efficacy of sugammadex compared with neostigmine on perioperative outcomes in patients with preoperative tracheal stenosis undergoing rigid bronchoscopy. Method We conducted a retrospective cohort study of adults who were diagnosed with primary or secondary tracheobronchial stenosis, and scheduled for interventional therapy under rigid bronchoscopy, at Shanghai Chest Hospital between December 2016 and July 2020. The exposure was categorized into two groups according to the antagonists of muscle relaxants administered after surgery: Group neostigmine vs. Group sugammadex. The primary outcome was the time to extubate after surgery, and the second outcome was the time to discharge from PACU. Perioperative adverse events were recorded. Results A total of 98 patients undergoing rigid bronchoscopy procedures were included. Patients in Group sugammadex showed less time to extubate (11 [8, 17] vs. 16 [12, 22] min, P = 0.003) and discharge from PACU (27 [20, 33] vs. 32.5 [24, 44] min, P = 0.013) than in Group neostigmine. The incidence and duration of hypotension during the procedure in Group sugammadex were significantly lower than that in Group neostigmine (18.5 vs. 40.8%, P = 0.038; 0 [0, 0] vs. 0 [0, 8] min, P = 0.036 respectively). Conclusions Sugammadex shortens the time to extubate and discharge from PACU in patients with tracheobronchial stenosis, accelerating postoperative recovery.